Validasi Instrumen Eksplorasi Etnomatematika pada Pembuatan Lomang (Lemang) di Kabupaten Kampar Riau - Nursyahfira; Zulfah; Astuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This study aims to produce a quality validation instrument for use in ethnomathematics exploration in the Making of Lomang (Lemang) in Kampar Regency, Riau. The research subjects consisted of 3 expert validators who had expertise in their fields. This study uses validity instruments. Research data were collected through observation sheets and interviews. Based on the results of the assessment of the interview sheet using the validation instrument, it can be concluded that the assessment sheet is in a very valid category. Therefore, the interview sheet has been deemed suitable and can be used to obtain assessment data and information related to research needs.